Analysis of Prospective Arabic Teachers’ Technological Pedagogical Content Knowledge (TPACK) - Zaimatuz Zakiyah; Muhammad Jafar Shodiq; Arrum Wijaya (IAIN Salatiga, 2022)
21st-century learning requires teachers to integrate technology into learning. Therefore, teachers need to improve their professional abilities in using technology. This research was conducted to obtain the TPACK profile of prospective Arabic language teachers who are currently studying for undergraduate program at Arabic Education department of IAIN Pekalongan. Furthermore, this research is survey research. Accordingly, primary data was collected by distributing questionnaires. In addition, researchers also used observation and documentation. In general, the TPACK for prospective Arabic teachers is categorized as